Chemopreventive effect of Phaleria macrocarpa on colorectal cancer aberrant crypt foci in vivo. (4th December 2016) - Shwter, Abdrabuh N.; Abdullah, Nor Azizan; Alshawsh, Mohammed A.; El-Seedi, Hesham R.; Al-Henhena, Nawal A.; Khalifa, Shaden A.M.; Abdulla, Mahmood A.
Abstract: Ethnopharmacological relevance: Natural products are important ingredients for pharmaceutical applications specifically new entities for treating cancer and other diseases. Phaleria macrocarpa is native of Indonesia and considered as a prolific source of bioactive substances useful for chemoprevention. Aim of the study: To investigate the chemopreventive properties of Phaleria macrocarpa on azoxymethane (AOM)-induced aberrant crypt foci (ACF) in rats. Methods: The biological activities of the ethanol extract of P. macrocarpa fruits were evaluated both in vitro and in vivo . First the extract was investigated for its in vitro antioxidant activity by the total phenolic content and ferric reducing antioxidant power assay. Then the chemopreventive effect of P. macrocarpa was performed on AOM-induced aberrant crypt foci as colorectal carcinoma model in rats. Result: the crude ethanolic extract of P. macrocarpa has high antioxidant activity and modulated the oxidative stress as proved by the up-regulation of glutathione-s-transferase and superoxide dismutase. Immunohistochemical staining of the treated sections showed overexpression of PCNA and Bax, reduced crypt sizes and numbers, indicating the characteristic feature of apoptotic cancer cells. PCNA is a landmark of cell damage and turn-over and can be associated with clinical cancer mutation. The most potent doses were 250 mg/kg and 500 mg/kg as compared to 35 mg/kg 5-fluorouracil. Conclusion: In this sense, the potential modulation of the colorectal pathophysiological pathway by P. macrocarpa natural compounds mostly flavonoids offer a great possibility for the discovery of new leads towards the colorectal cancer. Graphical abstract: